#REALTALK: Facebook Confessions pages as a data resource for academic and student support services at universities. Issue 4 (2nd October 2021) - Sacks, Benjamin; Gressier, Catie; Maldon, Justine
ABSTRACT: University students frequently use campus Facebook Confessions pages to engage with their peers about their university experiences. This article explores the utility of Confessions pages in providing novel data to aid the development of student services generally, and academic skills support in particular. Through a qualitative thematic analysis of five universities' Facebook Confessions pages over five years, our research demonstrates that these platforms provide valuable insights. Confessions data complement traditional research and evaluation approaches and enable academic skills advisors to tailor their practices in response to students' expressed needs. Additionally, these pages offer valuable insights into student learning and engagement styles, with the shift toward active and group pedagogical styles clearly evident. Yet overt interventions are likely to be unwelcome and counterproductive. We therefore suggest that while some limited participation can be beneficial, ultimately university staff should remain passive users of data, rather than active participants.